2003
DOI: 10.1375/bech.20.4.223.29379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thought Suppression on Subliminally and Supraliminally Presented Food-related Stimuli

Abstract: This study investigates whether hyperaccessibility occurs for supraliminally or subliminally presented sweets-related stimuli after prior suppression of thoughts about sweets. Thirty-three students (all female; 18—25 years old) participated in the experiment. In the first phase, half of the experimental group was instructed to suppress all sweets-related thoughts. The other participants were given control instructions. In the second phase, as part of a modified Stroop task, participants were asked to state the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Supraliminal threat cue priming may affect subsequent subliminal and supraliminal attentional patterns, as well outcomes and coping associated with biases (Luecken et al, 2004). Conscious attempts to divert attention from supraliminal cues may make these cues hyperaccessible at the subliminal level (Dejonckheere, Braet, & Soetens, 2003; Wegner, 1994). Second, although a 1250 ms interval between word pair presentation and target appearance is standard in studies of attentional bias studies in children, in college students, it is sufficiently long to allow movements of attention between the two stimulus words (Reed & Derryberry, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Supraliminal threat cue priming may affect subsequent subliminal and supraliminal attentional patterns, as well outcomes and coping associated with biases (Luecken et al, 2004). Conscious attempts to divert attention from supraliminal cues may make these cues hyperaccessible at the subliminal level (Dejonckheere, Braet, & Soetens, 2003; Wegner, 1994). Second, although a 1250 ms interval between word pair presentation and target appearance is standard in studies of attentional bias studies in children, in college students, it is sufficiently long to allow movements of attention between the two stimulus words (Reed & Derryberry, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who purposely attempt to avoid unwanted thoughts also may experience an increased priming of the to-be-suppressed thoughts (hyperaccessibility; Wegner & Erber, 1992). Despite the relatively few studies examining the association between thought suppression and eating behaviors, existing research does indicate the outcomes of thought suppression, such as hyperaccessibility and rebound, also result from attempting to suppress food-related thoughts (Dejonckheere, Braet, & Soetens, 2003; Smart & Wegner, 1999). …”
Section: 1 Introductionmentioning
confidence: 99%
“…The nascent research investigating the relationship between thought suppression and eating behaviors have reported mixed findings. Some studies [3,4,5,6,7] found that the outcomes of thought suppression, such as hyperaccessibility and rebound, do result from attempting to suppress food-related thoughts, whereas one study did not [8,9,10]. The latter study, however, [8] did not examine if the outcomes of thought suppression differed between participants who were currently dieting versus not or healthy weight versus overweight/obese, both of which appear to affect the outcomes of thought suppression [11–13].…”
mentioning
confidence: 99%